"Making Education Possible Again": Pragmatist Experiments for a Troubled and Down‐to‐Earth Pedagogy. Issue 4 (21st December 2022) - Thoilliez, Bianca
Abstract: In this article, Bianca Thoilliez draws on pragmatist notions of fallibilism and pluralism to develop proposals for possible educational interventions to address the problem of "post‐truth" conditions. Post‐truth, she contends, is not only a political danger for liberal democracies, but it also poses a serious threat of extinction for our educational practices. With the help of some of Bruno Latour's and Danna Haraway's categories, and with the narrative intervention of Gerald Durrell's My Family and Other Animals, Thoilliez attempts to adapt both Charles Peirce's and William James's classic pragmatist ideas in order to experiment with new horizons of thought capable of overcoming the exhausted pedagogical divides of docility/indocility, conserve/discard, and optimism/pessimism that often seem woven into the definition of educational relationships, the establishment of curriculum content, and the orientation of pedagogical actions. As an alternative, she recommends building communitarian alliances of fallibilistic inquiry and promoting practices of pluralistic cultural provision as more useful educational ends‐in‐view that embody a down‐to‐earth pedagogy capable of reinstating trust, taking care of truths, looking for ways of keeping our lives together, and making education possible again. Thus, here Thoilliez proposes a pedagogy that neither fixes nor evades our troubles, but one that stays with them.